2005
DOI: 10.1111/j.1439-0264.2005.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Macroanatomical Study of the Neurocranium in some Carnivora

Abstract: This study was carried out to investigate the specific anatomical features of the neurocranium of the skull of the dog, cat, badger, marten and otter. Twenty-five animals (five from each species) were used without sexual distinction. The neurocranium consists of os occipitale, os sphenoidale, os pterygoideum, os ethmoidale, vomer, os temporale, os parietale and os frontale. The processus paracondylaris is projected ventrally in the cat, dog, marten and badger, and caudally in the otter. Two foramina were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 3 publications
2
12
0
Order By: Relevance
“…The ventral direction of paracondylar processes is also observed in dogs, cats, badgers and martens (Karan et al 2006). We also found that both species investigated possess an oval-shaped foramen magnum.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…The ventral direction of paracondylar processes is also observed in dogs, cats, badgers and martens (Karan et al 2006). We also found that both species investigated possess an oval-shaped foramen magnum.…”
Section: Discussionsupporting
confidence: 50%
“…We also found that both species investigated possess an oval-shaped foramen magnum. The same shape for raccoon dogs was reported by Hidaka et al (1998), whereas for dogs, cats, badgers and martens by Karan et al (2006). Well-articulated zygomatic processes of the frontal bones are typical of dogs, badges and martens, whereas in cats they extend to the frontal processes of the zygomatic bones (Karan et al 2006).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The tympanic bulla is not well developed in Didelphis albiventris, unlike well developed in porcupine (Yilmaz 1998), ferret (He et al 2002), badger, otter, marten, cat, and dog (Karan et al 2006, Dyce et al 2010. There is no difference between bone formation found in the hard palate of the white-eared opossum skull and in the dog (Dyce et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The supraorbital foramen was absent in the white-eared opossum. In the raccoon, badger, otter, and marten skull, the supraorbital foramen was also absent (Yilmaz et al 2000, Dinc 2001, Karan et al 2006.…”
Section: Discussionmentioning
confidence: 99%